Early-Life Nutrition and Schooling - Droller, F (Elsevier Ltd, 2025)
We study a large supplemental nutrition program aimed at reducing malnutrition in Chile and its impact on the education of children ages 6–13. Using individual-level data from representative samples from the 1970, 1982, and 1992 national censuses, along with variation in milk distribution across provinces and over time, we estimate the effect of exposure to the milk program on years of schooling. We find that the impact was greatest for cohorts born between 1969 and 1976, a period of significant program expansion. The main effect implies an increase of 0.18 years of schooling due to exposure to the program, accounting for about 20% of the overall growth in educational attainment. These results show the substantial role of an early-life nutritional intervention in improving long-term educational outcomes for a significant portion of the population. © 2025 The Authors